Sentiment Classification Analysis of Tokopedia Reviews Using TF-IDF, SMOTE, and Traditional Machine Learning Models - Barus, Herianta; Fajri, Ika Nur; Pristyanto, Yoga (Politeknik Negeri Batam, 2025)
This study explores sentiment classification on Tokopedia user reviews using TF-IDF for feature extraction and SMOTE to handle class imbalance. From nearly one million raw reviews sourced from Kaggle (